Synthesis, Characterization and Antibacterial Evaluation of Some Coumarin Derivatives - T. Abduljabbar, Tariq; K. Hadi, Mohammed (Iraqi Journal of Pharmaceutical Sciences, 2021)
Coumarin derivatives have shown different biological activities, such as antifungal, antibacterial antiinflammatory, and antioxidant activities, besides antibiotic resistance modulating effects, and anti-HIV, hepatoprotective, and antitumor effect. So, new coumarin derivatives (hydrazones and an amide) were synthesized through multisteps reactions. All the synthesized target compounds were characterized by FT-IR spectroscopy, 1HNMR analysis. The compounds then evaluated for their anti-bacterial activity by means of well-diffusion method against two gram-positive bacteria (Staphylococcus aureus, Streptococcus pneumoniae) and two gram-negative bacteria (E.coli and Pseudomonas aeruginosa). The highest activity was demonstrate by compound k2 which found to be highly active against pseudomonas aeruginosa.